Alcohol Consumption and risk of Barrett’s Esophagus. Mini-review of recent literature - Nucci, Daniele; Gianfredi, Vincenza; Minelli, Liliana; Realdon, Stefano (Progress in Nutrition, 2018)
Alcohol consumption has a substantial importance in the causation of cancer of the oral cavity, pharynx, liver, colon, rectum; and in women, breast. It is also recognized as an independent risk factor for esophageal squamous cell carcinoma (ESCC). Nevertheless, the association with esophagus adenocarcinoma (EAC) is still not completely defined; as well as the association between alcohol intake and Barrett’s Esophagus (BE). The aim of this mini-review is to summarize recent findings from population studies focused on the association between alcohol consumption and risk of BE. The research was carried out in PubMed, filtering for studies conducted in the period 2009-2015. Our mini-review has shown no association between the consumption of alcohol and BE. Some type of alcoholic beverages has shown an inverse association. Direct public health applications of these findings are limited, considering the causal link between moderate-to-heavy alcohol consumption with increased risks of several cancers. Given the rising incidence of BE and EAC, it is important to understand the interplay of dietary and lifestyle factors that influence the development of these conditions.